Tabu Search and an Exact Algorithm for the Solutions of Resource-constrained Project Scheduling Problems - Omer Atli (International Journal of Computational Intelligence Systems, 2011)
When the project is scheduled with a given set of resources, it is difficult to find the optimal solution. Resourceconstrained scheduling problems (RCPSP) are generally NP-hard. In this paper, a high level heuristic procedure â€œTabu Search Algorithm (TSA)â€ is proposed to provide good solutions to resource-constrained, deterministic activity duration project scheduling problems. We present the application results of the computational tabu search and OPL-CPLEX algorithm and compare them with that of earlier applicable researches along with a discussion about further research. Our computational results are presented, which establish the superiority of tabu search over the existing heuristic algorithms. Two different solution strategies are also discussed, namely tabu search and OPLCPLEX exact algorithm approach which can be used with the proposed model. Due to the execution time, we have shown that OPL-CPLEXâ€™s algorithm is a valid method with medium scale RCPSPs. For the considered deterministic problems, a good agreement has been obtained between theoretical and experimental results.